Does Bitcoin hedge commodity uncertainty? - Khanh Hoang; Cuong Nguyen; Kongchheng Poch; Thang X. Nguyen (Journal of Risk and Financial Management, 2020)
This paper examines the connectedness between Bitcoin and commodity volatilities, including oil, wheat, and corn, during the period Oct. 2013-Jun. 2018, using time- and frequency-domain frameworks. The time-domain framework's results show that the connectedness is 23.49%, indicating a low level of connection between Bitcoin and the commodity volatilities. Bitcoin contributes only 2.55% to the connectedness, while the wheat volatility index accounts for 12.51% of the total connectedness. The frequency connectedness shows that Bitcoin's contribution to the total connectedness increases from high-frequency to low-frequency bands, and the total connectedness reaches up to 22.47%. It also indicates that Bitcoin is the spillover transmitter to the wheat volatility, while being the spillover receiver from the oil and corn volatilities. The findings suggest that Bitcoin could be a hedger for commodity volatilities.
Keywords: 330; Bitcoin; commodity; diversification; hedging; volatility spillover